DEWI AYU’S ELECTRA COMPLEX AS SEEN IN EKA KURNIAWAN’S BEAUTY IS A WOUND - Handoko, Putut; Kartika, Dwi Indah (Faculty of Letters, Dr. Soetomo University, 2016)
This study aims to analyze Dewi Ayu?s Electra Complex as Seen in Eka Kurniawan?s Beauty Is A Wound. The objectives of the study are: (1) to find out the proofs of Dewi Ayu?s Electra Complex as Seen in Eka Kurniawan?s Beauty Is A Wound; (2) to find out the causal factors of Dewi Ayu?s Electra Complex as Seen in Eka Kurniawan?s Beauty Is A Wound; and (3) to find out the effects of Dewi Ayu?s Electra Complex on herself and on Ma Gedik as Seen in Eka Kurniawan?s Beauty Is A Wound. The theory used by the thesis writer is the theory of Electra Complex by Freudian theories in psychoanalysis approach and she also applies a qualitative research. Keywords: Psychoanalysis, Electra complex, Defence Mechanism.